2011
DOI: 10.1063/1.3633474
|View full text |Cite
|
Sign up to set email alerts
|

Cluster cross sections from pickup measurements: Are the established methods consistent?

Abstract: Pickup of several molecules, H 2 O, HBr, and CH 3 OH, and Ar atoms on free Ar N clusters has been investigated in a molecular beam experiment. The pickup cross sections of the clusters with known mean sizes,N ≈ 150 and 260 were measured by two independent methods: (i) the cluster beam velocity decrease due to the momentum transfer of the picked up molecules to the clusters, and (ii) Poisson distribution of a selected cluster fragment ion as a function of the pickup pressure. In addition, the pickup cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 61 publications
(94 reference statements)
1
48
0
1
Order By: Relevance
“…We have observed the variation of the pickup cross section for various molecules already previously for argon clusters. 7 The pickup cross section is determined by the strength and extent of the interaction potential between the picked-up molecule and the cluster constituents and also by the mass of the molecule and relative velocity. The later issue is discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have observed the variation of the pickup cross section for various molecules already previously for argon clusters. 7 The pickup cross section is determined by the strength and extent of the interaction potential between the picked-up molecule and the cluster constituents and also by the mass of the molecule and relative velocity. The later issue is discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…IV. The previous investigations 7,8 showed that this simple model described the final velocity dependence very accurately for argon clusters.…”
Section: B Pickup Cross Sectionmentioning
confidence: 99%
See 3 more Smart Citations